2012
DOI: 10.1093/ilar.53.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Documented and Potential Research Impacts of Subclinical Diseases in Zebrafish

Abstract: The zebrafish (Danio rerio) has become a very important animal model in biomedical research. In contrast to other models, such as mice, there has been relatively little documentation or control of subclinical disease in zebrafish research facilities. Several infectious and non-infectious conditions are consistently detected by histopathology in apparently healthy D. rerio. The most commonly observed infectious agent in zebrafish is Pseudoloma neurophilia, which is a microsporidian organism that targets the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 41 publications
1
92
0
Order By: Relevance
“…2 Infected fish are often asymptomatic; however, emaciation and skin darkening may also be evident. 3 On histopathological examination, cross sections of nematodes embedded in the mucosal epithelium may be observed as well as severe inflammatory changes in the intestine and coelomic cavity. 3 Characteristic double-operculated barrel-shaped eggs may also be visualized in the gut lumen.…”
Section: Introductionmentioning
confidence: 99%
“…2 Infected fish are often asymptomatic; however, emaciation and skin darkening may also be evident. 3 On histopathological examination, cross sections of nematodes embedded in the mucosal epithelium may be observed as well as severe inflammatory changes in the intestine and coelomic cavity. 3 Characteristic double-operculated barrel-shaped eggs may also be visualized in the gut lumen.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of granulomas confounds histopathology data in a number of studies. 3 Parikka et al showed that M. marinum upregulates various inflammatory cytokines that may confound immunological research. 29 Infection with this species has been documented to alter gene expression in several studies.…”
Section: Choice Of Agentsmentioning
confidence: 99%
“…When reporting results from a study utilizing an animal research model, it is important to describe the health status of the animals, including the presence or absence of clinical or subclinical infection. 1 Failure to report presence of disease can lead to misinterpretation of research results from zebrafish 2,3 and mammalian models [4][5][6] and result in published studies becoming unusable or nonreplicable. 7 Subclinical infections in zebrafish can result in confounded experimental results, misinterpretation of experimental data, poor reproducibility, and the unnecessary utilization of more animals to demonstrate statistical significance.…”
mentioning
confidence: 99%
“…2 As a result, there is increasing awareness of the importance of chronic infections of laboratory zebrafish. 3 Zebrafish are a very popular tropical fish for home aquariums and there are numerous reports of zebrafish being obtained from retail pet stores and used in research. 4,5 Indeed, virtually all zebrafish lines, even those currently maintained in laboratory fish facilities, were originally derived from retail pet store fish.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 As P. neurophilia has only been described from one fish species since its initial report in 1980, it may be assumed that this parasite has very narrow host specificity. However, the observation of P. neurophilia infecting a moribund Betta splendens that was cohabitating with zebrafish in a personal home aquarium for several months led us to realize that this assumption was incorrect, and thus, we were interested in investigating the ability of this parasite to infect other laboratory fishes.…”
Section: Introductionmentioning
confidence: 99%